Deshelled Carica papaya seeds as natural coagulant for improvement quality of river water - Amir Hariz Amran,; Nur Syamimi Zaidi,; Khalida Muda,; Muhammad Burhanuddin Bahrodin,; Liew, Wai Loan (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study evaluated the efficiency of deshelled papaya seeds as the natural coagulant in improving quality of river water. The deshelled papaya seeds biomass was mainly characterized for functional groups using FTIR, surface charge and protein content. Coagulation and flocculation tests were conducted using batch test for various dosages and pH values. The optimum dosage and pH were then tested in treating river of Class III to Class V. The functional groups in deshelled papaya seeds were O-H, C=O and C-O groups. The surface charge and protein content was +0.4 meq/g and 363 mg/g, respectively. The deshelled papaya seeds coagulant was able to remove turbidity up to 87.6 and 88.3% for river of Class III and Class IV, respectively, as well as 57.6 and 62.1% of total coliform and Escherichia coli, respectively, from Class III river at dosage 196 mg/L and pH 4. This study demonstrated that the deshelled Carica papaya seedsderived coagulant is capable in treating common pollutants of river and simultaneously shows antibacterial properties.